Unions as insurence: Employer-worker risk sharing and workers' outcomes during COVID-19 - Nils Braakmann; Boris Hirsch (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2023)
We investigate to what extent workplace unionisation protects workers from external shocks as predicted by models of implicit contracts. Using the COVID-19 pandemic as a plausibly exogenous shock hitting the whole economy, we compare workers who worked in unionised and non-unionised workplaces directly before the pandemic in a difference-in-differences framework. We find that unionised workers were substantially more like to remain working for their pre-COVID employer, at their pre-COVID workplace, in their pre-COVID job and to be in employment. This greater employment stability was not traded off against lower working hours or labour income.
Keywords: J51; I18; I19; J63; 330; Unions; risk-sharing; implicit contracts; insurance effects; COVID-19